2008
DOI: 10.1002/ca.20680
|View full text |Cite
|
Sign up to set email alerts
|

The association of proximal femur geometry with hip fracture risk

Abstract: We aimed to discuss the risk assessments of patients with hip fractures due to the fall-related moderate or minimal trauma and compare them with non-fractured control patients by bone mineral density (BMD) and proximal femur geometric measurements to assess whether geometric measurements of femoral dimensions were associated with femoral strength and hip fracture risk. Forty-two osteoporotic patients with proximal femur fracture and 40 osteoporotic non-fractured age and gender-matched controls were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…It has been established that the thickness in the femoral neck coincides with diminished production of endosteal bone, having as a result a loss of bone density (Bone Mineral Density -BMD), and a rise in sub periosteal bone, secondary to the production generated at growth (Dinçel et al, 2008). In a retrospective study, El-Kaissi et al (2005) demonstrated that Caucasian postmenopausal women with hip fractures have a longer length and axis of the femoral neck, compared to women without fractures, determining that, independent of their age, height and bone density, the risk of hip fracture increases by 24% with every one millimeter increase in the thickness of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the thickness in the femoral neck coincides with diminished production of endosteal bone, having as a result a loss of bone density (Bone Mineral Density -BMD), and a rise in sub periosteal bone, secondary to the production generated at growth (Dinçel et al, 2008). In a retrospective study, El-Kaissi et al (2005) demonstrated that Caucasian postmenopausal women with hip fractures have a longer length and axis of the femoral neck, compared to women without fractures, determining that, independent of their age, height and bone density, the risk of hip fracture increases by 24% with every one millimeter increase in the thickness of the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…This is because a longer lever arm is considered to increase the risk of fracture on impact [3]. As HAL increases, the lever arm between the hip center and the femur extends and fractures can occur with the excess load on the proximal femur [9]. Although patients with femoral neck fractures have been reported to show longer HAL [11,[16][17][18], when compared with patients with trochanteric fractures, no significant differences in lever arm indices such as HAL, FNAL, or head offset were found between groups in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, risk factors of a proximal femoral fracture may be associated with femoral geometry and BMD values [9]. Several studies have shown that variations in femoral geometric measurements such as hip axis length (HAL) [14], neck shaft angle (NSA) [2], and femoral neck width are associated with increased risk of proximal femoral fractures [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…1,17 Besides in a recent study, we evaluated the bone morphogenetic proteins, mostly focusing on the usefulness of biochemical markers for risk assessment. 16 Here, our goal was to better understand IDO's role in bone metabolism via two different anatomical types of hip fracture groups compared to healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The complex pathogenesis of osteoporosis is determined by the interaction of genetic, metabolic, and multiple environmental factors. Besides, free radicals and reactive oxygen species may involve in bone metabolism in which oxidative stress promotes the apoptosis of osteoblasts and the survival of osteoclasts.…”
mentioning
confidence: 99%